Drugs by Numbers: Reaction‐Driven De Novo Design of Potent and Selective Anticancer Leads1. Issue 17 (20th November 2012) - Spänkuch, Birgit; Keppner, Sarah; Lange, Lisa; Rodrigues, Tiago; Zettl, Heiko; Koch, Christian P.; Reutlinger, Michael; Hartenfeller, Markus; Schneider, Petra; Schneider, Gisbert
<x xml:space="preserve">Abstract</x> A potent and selective inhibitor of the anticancer target Polo‐like kinase 1 was found by computer‐based molecular design. This type II kinase inhibitor was synthesized as suggested by the design software DOGS and exhibited significant antiproliferative effects against HeLa cells without affecting nontransformed cells. The study provides a proof‐of‐concept for reaction‐based de novo design as a leading tool for drug discovery.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>